Approaches to deep learning based manipulating strategy reconstructions for complex chemical processes. (November 2021) - Li, Hongguang; Tang, Xiaojie; Zhao, Wenjing; Yang, Bo
Abstract: Modern complex chemical process operations produce a large amount of process monitoring and control time series data, which are potentially useful to extract valuable operating experiences and manipulating rules to improve the intelligence of process operations. Previous researches show that time series clustering is an effective method to mine historical control sequences. However, the actual working conditions often deviate from the historical data, making it difficult to reconstruct accurate process regulation manipulating strategies. In response to this problem, this paper proposes a manipulation strategies reconstruction method using a convolutional neural network model (MSR-CNN). Therein, the time series are hierarchically clustered according to the Levenshtein distance to obtain different classes of process disturbance states, and the corresponding manipulated sequences fragments obtained are treated with a symbolic aggregation approximation. Then the improved convolutional neural network is used for deep learning and manipulation strategies reconstruction of the process disturbance states and the corresponding manipulating sequences strings. Finally, applying to a numerical example and an ethanol–water distillation tower unit, the proposed method is proved to be effective. Compared with traditional supervisory control methods, our contributions can help well construct complex chemical process control strategies less dependent on human operators' operating experiences. Highlights: Agglomerative hierarchical time series clustering based on levenshtein distance. Fragmentation of effective manipulation sequences. Deep learning and reconstruction of manipulation strategies with convolutional neural networks. Favorable comparison with the supervisory control method.